2019
DOI: 10.1186/s40691-019-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic antecedents and apparel customization: moderating effects of gender

Abstract: The impact of gender is critical in consumer behavior; however, gender differences have been overlooked in consumer studies. The purpose of this study is to examine how behavior-inducing psychogenic needs (i.e., need for uniqueness, self-promotion, and social identity) influence the way individuals perceive apparel customization, leading to buying intention of customized apparel products. Further, to identify whether gender plays a moderating role in the relationships between those psychogenic needs and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Previous studies have scrutinized the effect of customization. For instance, Seo and Lang (2019) researched apparel product customers and found that customization caused a higher level of purchase intention. Coelho and Henseler (2012) studied banking and cable TV service users, and revealed that customization is essential for positive customer attitudes (e.g.…”
Section: H3mentioning
confidence: 99%
“…Previous studies have scrutinized the effect of customization. For instance, Seo and Lang (2019) researched apparel product customers and found that customization caused a higher level of purchase intention. Coelho and Henseler (2012) studied banking and cable TV service users, and revealed that customization is essential for positive customer attitudes (e.g.…”
Section: H3mentioning
confidence: 99%
“…The concept of design argumentation is aimed at the targeted management of hypothetical models of the style image of the product from the point of view of typifying the design and manufacturing processes at an enterprise [7]. The social role of style in behavior for purchasing an assortment model is determined by the valence of communications in the dimensional scale of image uniqueness from the position of the consumer [8]. Accordingly, studies aimed at increasing the mobility of flexible reorientation of the production of the established assortment by means of regulating the positive perception of style individualization should be considered relevant.…”
Section: Introductionmentioning
confidence: 99%
“…23 Customers, therefore, want fashion to express their individuality and ideas by way of design elements such as images and colors. 41,42 Hence, there is a need for fashion design systems that help ordinary people design fashions that appeal to them. 3,43 Such customer-design systems have been developed in recent years.…”
Section: Design-support Systems For Fashionmentioning
confidence: 99%